1988
DOI: 10.1007/bf00049423
|View full text |Cite
|
Sign up to set email alerts
|

Monotonicity of quadratic-approximation algorithms

Abstract: Maximum likelihood estimation, curvature, monotonicity, algorithms, Newton-Raphson algorithm,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
153
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(156 citation statements)
references
References 11 publications
2
153
0
1
Order By: Relevance
“…Similar to the bounding approach of the EM algorithm, the results in Bohning and Lindsay (1988) show that finding θ 1 that maximizes the right hand side of eq. (11) implies that l(θ 1 ) ≥ l(θ 0 ) with equality only at θ 1 = θ 0 .…”
Section: The Gem Algorithmmentioning
confidence: 91%
See 2 more Smart Citations
“…Similar to the bounding approach of the EM algorithm, the results in Bohning and Lindsay (1988) show that finding θ 1 that maximizes the right hand side of eq. (11) implies that l(θ 1 ) ≥ l(θ 0 ) with equality only at θ 1 = θ 0 .…”
Section: The Gem Algorithmmentioning
confidence: 91%
“…The method is based off of an important result in Bohning and Lindsay (1988) which says that for a twice differentiable, concave function l(θ), if there exists a symmetric, negative definite matrix B such that B ≤ 2 l(θ 0 ) for all values of θ 0 , then for any value θ, the following is true.…”
Section: The Gem Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, by majorizing the surrogate -finding its current maximum value -it can be shown that stepping to this value results in an increase in the value of the original objective function. A viable surrogate function for the log-likelihood function for dichotomous data was given in [28] and was extended to the multinomial situation in [6]. Iteration then results in convergence to the unique maximum.…”
Section: Methods and Theorymentioning
confidence: 99%
“…an additive or multiplicative way may be useful, at least for exact Hessian matrices and their regularization. Note also that numerical approximations of the Hessian matrix exist in the literature, and from [49] a justification of the approach can be derived.…”
Section: Derivatives Of the Objective Functionmentioning
confidence: 99%